2013
DOI: 10.3174/ajnr.a3511
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread White Matter Alterations in Patients with End-Stage Renal Disease: A Voxelwise Diffusion Tensor Imaging Study

Abstract: BACKGROUND AND PURPOSE:ESRD results in excessive accumulation of urea and toxic metabolites. Hemodialysis is usually performed to maintain health in patients with ESRD; however, it may cause silent white matter alterations in the earlier stages. Hence, this study aimed to perform voxelwise diffusion tensor analysis for global detection of subtle white matter alterations in patients with ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 28 publications
9
50
1
1
Order By: Relevance
“…Results of prior studies (23,(27)(28)(29) have shown that analysis of functional connectivity determined by measuring blood oxygenation level-dependent fluctuations is regarded to be more flexible than analysis of structural connectivity, which is the substrate of functional connectivity. These imaging findings are supported by neuropsychologic results in our study and prior studies (9)(10)(11)(12)(13). We found that neuropsychologic results correlated with change in temporal correlation coefficients of the fiber bundles connecting the PCC and with the change in digit symbol test scores (r = 0.533, P = .013) (Fig 4c).…”
Section: Correlation Analysis Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Results of prior studies (23,(27)(28)(29) have shown that analysis of functional connectivity determined by measuring blood oxygenation level-dependent fluctuations is regarded to be more flexible than analysis of structural connectivity, which is the substrate of functional connectivity. These imaging findings are supported by neuropsychologic results in our study and prior studies (9)(10)(11)(12)(13). We found that neuropsychologic results correlated with change in temporal correlation coefficients of the fiber bundles connecting the PCC and with the change in digit symbol test scores (r = 0.533, P = .013) (Fig 4c).…”
Section: Correlation Analysis Resultssupporting
confidence: 92%
“…Diffusion-tensor imaging (DTI) studies showed that patients with ESRD have lower fractional anisotropy and increased mean diffusivity values in all white matter regions when compared with patients in a healthy control group. These results positively correlated with neuropsychologic scores (13)(14)(15)(16). In recent studies (17)(18)(19)(20) of resting-state functional MR imaging, investigators have shown abnormal brain functional connectivity, particularly in the default mode network (DMN), in patients with ESRD.…”
Section: Discussionmentioning
confidence: 52%
“…Authors of these studies did not investigate the effect of the specific dialysis modality on spontaneous brain activity in patients with ESRD, because they included patients undergoing hemodialysis and PD and those not undergoing dialysis. In addition, most previous studies have been focused on abnormal gray and white brain matter structures (16,(22)(23)(24)(25)(26). Several studies (2,7,8) included patients with ESRD undergoing hemodialysis and PD, which can have a confounding effect on the study results.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 These studies reported decreased FA and increased mean diffusivity and RD in patients on HD compared with age-matched controls, indicating established WM damage. However, the lack of a longitudinal design in these studies does not allow any causality inference linking HD as a process to WM damage.…”
Section: Discussionmentioning
confidence: 99%